Influence of different substrates on seed germination of Ziziphus joazeiro Mart., Rhamnaceae - Moniz-Brito, Kátia Lidiane; Ayala-Osuña, Juan Tomás (SITIENTIBUS série Ciências Biológicas, 2005)
Ziziphus joazeiro is a typical Brazilian tree of the northeastern dry lands, being endemic to the Caatinga. It occurs in various states of Northeast Brazil and provides a great economic potential and importance for this semi-arid region. The objective of this research was to compare the germination capacity and the vigor of seeds of Z. joazeiro submitted to different sowing substrates in field conditions. The diaspores were submitted to chemical scarification with sulfuric acid concentrated for 20 minutes. They were later sown in these substrates: organic soil + sand, organic soil + vermiculite, and organic soil + sawdust. Results indicate that the substrate organic soil + vermiculite is the most recommended when there is the intention to acquire more vigorous seedlings, since it influences positively the initial growth of plantules.